O papel da sedimentoscopia urinária no diagnóstico de doença vesical em cães - De Vasconcellos, Amanda Leal [UNESP]; De Vasconcellos Aquino, Gabriel [UNESP]; Galvão, André Luiz Baptista [UNESP]; Carvalho, Marileda Bonafim [UNESP] (My University, 2013)
In order to evaluate the role of sedimentoscopy of urine samples in the diagnosis of bladder diseases, were evaluated 46 dogs, 23 males and 23 females with clinical sign of bladder disease or by request of checkup. Sedimentoscopy proved to be a diagnostic test with 100% specificity and positive predictive value, 93.5 % accuracy and 82.4 % negative predictive value for bladder disease cases. It was concluded that this examination must be included in the evaluation of the urinary tract in dogs.
The role of urinary sedimentoscopy for bladdler disease diagnosis in dogs
Keywords: Cystitis; Diagnostic; Dog; Urinary sediment